2020
DOI: 10.1097/ogx.0000000000000747
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia Among African American Pregnant Women: An Update on Prevalence, Complications, Etiology, and Biomarkers

Abstract: Importance Preeclampsia is a devastating disease of pregnancy associated with increased risk of fetal and maternal complications. African American pregnant women have a high prevalence of preeclampsia, but there is a need of systemic analyses of this high-risk group regarding complications, etiology, and biomarkers. Objective The aim of this study was to provide a synopsis of current research of preeclampsia specifically related to African American wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 92 publications
0
24
0
1
Order By: Relevance
“…Similarly, women with pregnancy complications who received doula care showed a 54% reduction in odds of PPA/PPD diagnosis, relative to similar women without doula care. Because Black women have a higher prevalence of some of the most common conditions women can acquire during pregnancy, including pre-eclampsia, 25 anemia, 26 and symptoms of depression or anxiety, 27 doula care targeted toward Black women may help bridge the gap in health outcomes between White and Black women enrolled in Medicaid. Our study findings suggest that doulas help mitigate the effects of high risk pregnancy characteristics on maternal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, women with pregnancy complications who received doula care showed a 54% reduction in odds of PPA/PPD diagnosis, relative to similar women without doula care. Because Black women have a higher prevalence of some of the most common conditions women can acquire during pregnancy, including pre-eclampsia, 25 anemia, 26 and symptoms of depression or anxiety, 27 doula care targeted toward Black women may help bridge the gap in health outcomes between White and Black women enrolled in Medicaid. Our study findings suggest that doulas help mitigate the effects of high risk pregnancy characteristics on maternal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Eclampsia affects about (5-8%) of all pregnancies, the recent report of the World Health Organization (WHO) shows that statistics suggest 76,000 maternal mortality and morbidity annually worldwide and about 500,000 child deaths due to Preeclampsia [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the discovery of new diagnostic markers and therapeutic targets is beneficial to the treatment of PE. 16 A previous study showed that in human melanomas, RORA, as a target of hypoxia-inducible factor 1 alpha, was up-regulated in hypoxia. 17 Furthermore, Qiu, et al 18 19 reported that the SNPs of RORA in the placental genome were associated with placental abruption risk.…”
Section: Discussionmentioning
confidence: 99%